(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Literature reviews are commonly used to seek evidence of health interventions. Studies have raised searching-related problems of Behavior Analytical interventions evidence. The present article was aimed to assess the usability of an academic curricular data-base (Plataforma Lattes) for searching of behavior analysis articles, which present health-related interventions. A search by knowledge area was made by keywords “Health Psychology” and “Behavior Analysis”. Founded academic curricula were selected for searching of published articles in the past five years. The curricula data base was a possible tool for setting up information — evidence — of behavioral interventions for health area.